The Role of Management Accounting in Long-Term Project and Investment Management - Arifiansyah Saputra; Siti Mialasmaya; Rahmad Rahmad (PT. Anagata Sembagi Education, 2024)
This study aims to explore the role of management accounting in long-term project and investment management. Management accounting plays a very important role in supporting effective decision-making, budget planning, cost control, and performance evaluation in projects and investments that require long-term commitment. Through literature study, this study examines various concepts, theories, and techniques of management accounting applied in project and investment management, including cost analysis, return on investment (ROI) calculation, and cash flow control. The results of the study indicate that management accounting not only functions as a recording and reporting tool, but also as a planning and monitoring tool that is very vital in minimizing risk and optimizing resource use. This study also identifies challenges in the application of management accounting, such as market uncertainty and changes in the economic environment that can affect the results of projects and investments. Overall, the application of good management accounting principles can improve operational efficiency, support more informed decision-making, and ensure the achievement of the company's long-term goals.